Constitutional Judge - Baamonde Gómez, Laura (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
This is a brief essay that aims to condense the most relevant aspects of the concept of «constitutional judge». Starting from highlighting the importance of studying these issues, which are directly connected with the very notion of legitimacy of the Constitutional Court as a body that closes the system and of counter-majority logic, its legal status will be analyzed in a broad sense. In other words, issues related to the constitutional composition scheme, the temporal aspects of the regulation of the mandate, as well as the set of prerogatives and restrictions that accompany the stay in office will be addressed. All this studied from the dichotomy physiology –the «should be» that imposes the normative frame of reference–/ pathology –the «be» often pernicious of its practical application.
Keywords: judge; Constitutional Court; legal status; mandate; pathology